2008
DOI: 10.1590/s1415-790x2008000400002
|View full text |Cite
|
Sign up to set email alerts
|

Serviço de Atendimento Móvel de Urgência (SAMU): análise da demanda e sua distribuição espacial em uma cidade do Nordeste brasileiro

Abstract: O município de Olinda, Pernambuco, criou instrumento para armazenamento de dados dos formulários das ocorrências do Serviço de Atendimento Móvel de Urgência (SAMU-192) e de forma pioneira georreferencia os atendimentos realizados. Objetiva-se descrever o perfil epidemiológico das ocorrências atendidas no município, de fevereiro (implantação do serviço) a junho de 2006, com ênfase na distribuição espacial das ocorrências mais relevantes. Foram utilizados dados secundários do banco de dados SAMU-192, considerand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
39

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 5 publications
2
12
0
39
Order By: Relevance
“…Similar results were found in other studies [4][5][6][7]14,31,33,34 . According to the World Health Organization (WHO), these groups are about three times more likely to die in a transportation accident than young women 3 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar results were found in other studies [4][5][6][7]14,31,33,34 . According to the World Health Organization (WHO), these groups are about three times more likely to die in a transportation accident than young women 3 .…”
Section: Discussionsupporting
confidence: 92%
“…When observing services according to day of the week and time of the accident, Friday had the most occurrences. However, other studies 33,34,42,43 reported that the highest frequency of transportation accidents occurred on Sundays, probably due to a greater number of commemorative events, among other factors, such as alcohol consumption, passing at high speeds, and risky maneuvers.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The reality in the capital of Paraiba is configured with the data of the country with regard to assistance toward elderly population as greater demand for requests to the SAMU for attendances to clinical aggravations. The attendances of SAMU in Recife-PE in higher percentage (71.5%) hypertension among the other occurrences, 11 clinics corroborating this way, with the data of the present study.…”
Section: Pbsupporting
confidence: 92%
“…In Brazil, demands made to the Serviços de Atendimento Móveis de Urgência -SAMU 192 (Mobile Emergency Care Services) have been focused on clinical health problems. This characteristic was identified in the following Brazilian cities: Ribeirão Preto, in the state of São Paulo, totaling 54.9% of all treatments (2) ; Olinda, in the state of Pernambuco, 57% (3) ; and Porto Alegre, in the state of Rio Grande do Sul, 64.8% (4) . Data are in agreement with morbidity and mortality indicators and national risk factors (5) , which show that clinical health problems are more prevalent and responsible for high disease and death indices.…”
Section: Introductionmentioning
confidence: 92%